Harnessing Edaphic Microalgae for Soil Carbon Sequestration and Climate-smart Agriculture - , Sanjay Swami; , Michelle C. Lallawmkimi; , Vikas Singh; , Kamlesh Kumar Yadav; , S. Alagendran; , Sanjay Koushal; , Guneshori Lairenjam (Archives of Current Research International, 2025)
Edaphic microalgae are emerging as critical components in climate-smart agriculture due to their multifaceted roles in enhancing soil health, sequestering carbon, and improving agricultural sustainability. These microorganisms, including cyanobacteria, green algae, and diatoms, fix atmospheric carbon through photosynthesis and contribute to the formation of soil organic matter (SOM) by releasing biomass and extracellular polymeric substances (EPS). Their ability to enhance soil aggregation, improve nutrient cycling, and stabilize carbon makes them essential in mitigating climate change. Advances in microalgal cultivation techniques, such as photobioreactors and biofilm-based systems, have improved their scalability, while omics technologies provide insights into their genetic and metabolic pathways, enabling bioengineering for enhanced functionality. Field studies demonstrate significant benefits, including increases in soil organic carbon by 15–30% and crop yield improvements of up to 20% when microalgae are applied as biofertilizers. Challenges such as environmental limitations, competition with other soil microorganisms, and high production costs hinder their widespread adoption. Future lie in exploring diverse microalgal species, developing cost-effective cultivation systems, and integrating microalgae into multifunctional agricultural systems like agroforestry and aquaponics. Policy support, including financial incentives and standardized regulations, will be instrumental in fostering adoption. Remote sensing and modelling tools further enhance the feasibility of large-scale applications, enabling precise monitoring of microalgal activity and contributions to soil carbon dynamics. Despite current limitations, the potential of edaphic microalgae to revolutionize sustainable agriculture is immense, offering scalable solutions to global challenges such as soil degradation, climate change, and food insecurity. With continued research, innovation, and interdisciplinary collaboration, edaphic microalgae could serve as a cornerstone for achieving resilience and sustainability in agriculture, aligning with global climate action goals and fostering long-term environmental and economic benefits.